ANALISIS KERENTANAN PENGELOLAAN WILAYAH PESISIR DITINJAU DARI PRESPEKTIF MITIGASI BENCANA DI KABUPATEN BADUNG PROVINSI BALI - Ikhsan Ikhsan; Abdul Rauf; Asbar Asbar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
The vulnerability identification of coastal areas in this study consisted of the level of danger (earthquake and tsunami), physical vulnerability and non-physical vulnerability. Determination of hazard level using modeling based on seismic history in the subduction zone south of Bali, while analysis of the level of physical and non-physical vulnerability is used Descriptive analysis and Analytical Hierarchy Process (AHP). The analysis process will determine the ranking used as an indicator of decision making to create a vulnerability level map in the research area through the Geographic Information System (GIS) with three levels, namely high, medium and low. In this study also formulated coastal area management policies in the perspective of disaster mitigation using SWOT analysis. The results of the analysis show that four kelurahan in Badung Regency which have high levels of vulnerability are Kuta, Tuban, Kedonganan and Tibubeneng. While the seven kelurahan in the medium level of vulnerability are Jimbaran, Benoa, Tanjung Benoa, Legian, Seminyak, Canggu, Dalung, and the four kelurahan with low levels of vulnerability are Pecatu, Ungasan, Kutuh and Kerobokan. In general the research area is at a high to moderate level of vulnerability, this shows that a comprehensive disaster mitigation effort is needed by implementing several strategies formulated, including 1) developing disaster resilient village programs by establishing disaster risk reduction forums and volunteer training villages for disaster mitigation, 2) maximizing community knowledge in disaster and mitigation to cope with high earthquake and tsunami hazard levels, 3) implementing regional regulations on disaster mitigation based spatial planning effectively in controlling disaster risk areas and utilizing green lines as evacuation routes and meeting point.